Synthesis, optical and magnetic properties of a new nanocomposite HAp/CoFe2O4/RGO. (1st December 2017) - Sakhaei, Fatemeh; Salahi, Esmaeil; Olya, Mohammad Ebrahim; Mobasherpour, Iman
Abstract : Magnetically separable CoFe2 O4 /reduced graphene oxide (CoFe2 O4 /RGO) and a new of magnetic hydroxyapatite/CoFe2 O4 /RGO nanocomposites (HAp/CoFe2 O4 /RGO) were prepared via co‐precipitation along with hydrothermal methods. The characterisation and properties of the synthesised nanocomposite were analysed using Fourier transform infrared, X‐ray powder diffraction, vibrating sample magnetometer, field emission scanning electron microscopy, transmission electron microscopy (TEM) and UV‐visible spectroscopy. TEM images show that the synthetic RGO layers are decorated with 10 nm CoFe2 O4 particles and HAp nanorods of about 10 nm diameter and 100 nm average length are well separated and uniformly distributed. In addition, separation of the layers from one another and approximately uniform distribution on nanosheets is completely visible. Due to the magnetic properties of HAp/CoFe2 O4 /RGO nanocomposite, it can be separated from the environment by an external magnetic field. In addition, the energy gap measurements represent the effective role of CoFe2 O4 /RGO inremarkable decreasing of the energy gap of the nano‐HAp.